C–H activation in IrIII and N-demethylation in PtII complexes with mesoionic carbene ligands: examples of monometallic, homobimetallic and heterobimetallic complexes12. Issue 42 (7th October 2015) - Maity, Ramananda; Tichter, Tim; van der Meer, Margarethe; Sarkar, Biprajit
Abstract : Mononuclear Pt II and the first dinuclear Pt II complexes along with a cyclometalated heterobimetallic Ir III /Pd II complex bearing mesoionic carbene donor ligands are presented starting from the same bis-triazolium salt. Abstract : Mononuclear Pt II and the first dinuclear Pt II complexes along with a cyclometalated heterobimetallic Ir III /Pd II complex bearing mesoionic carbene donor ligands are presented starting from the same bis-triazolium salt. The mononuclear Pt II complex possesses a free triazole moiety which is generated from the corresponding triazolium salt through an N -demethylation reaction, whereas the mononuclear Ir III complex features an unreacted triazolium unit.